Software System Model Correctness using Graph Theory: A Review (Global Journal of Computer Science and Technology, 2023)
The Unified Modeling Language UML is the de facto standard for object-oriented software model development The UML class diagram plays an essential role in design and specification of software systems The purpose of a class diagram is to display classes with their attributes and methods hierarchy generalization class relationships and associations general aggregation and composition between classes in one model
Keywords: UML models; UML class diagrams; software engineering; model correctness; graph theory